Diagnostic value of exosome derived long noncoding RNA in gastric cancer in Chinese population: A PRISMA-compliant systematic review and meta-analysis. Issue 51 (23rd December 2021) - Zhu, Kangle; Yang, Jinxian; Zhu, Huixia; Wang, Qingqing
Abstract: Background: Objective to systematically evaluate the diagnostic value of long noncoding RNA (lncRNA) in gastric cancer (GC) in the Chinese population. Methods: PubMed, Web of Science, EMBASE, Cochrane Library, CNKI, and Wanfang Database were searched. According to the search strategy and inclusion and exclusion criteria, 2 staff members screened the relevant kinds of literature from January 2010 to December 2020 and extracted the relevant data. Revman5.3, Meta-Disc1.4, and Stata15.1 software were used to analyze the relationship between lncRNA from exosomes and the diagnosis of GC. The combined values of sensitivity (SEN), specificity (SPE), positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio (DOR) and their corresponding 95% confidence intervals (CIs) were calculated. The summary receiver operating characteristic curve was drawn and the area under the ROC curve (AUC) value was calculated. Results: In 9 studies, 1314 samples were included, including 792 cases in the case group and 522 cases in the control group. The combined SEN was 0.82 (95% CI: 0.77–0.86), the combined SPE was 0.78 (95% CI: 0.72–0.83), the combined positive likelihood ratio was 3.7 (95% CI: 2.9–4.6), the negative likelihood ratio was 0.23 (95% CI: 0.18–0.29), and the DOR was 16 (95% CI: 12–23), AUC was 0.87 (95% CI: 0.84–0.90). Subgroup analysis showed that the SEN, SPE, likelihood ratio, DOR, and AUC of plasma-derived lncRNA in the diagnosis of GC were better than those of serum. Conclusions: Exosome-derived lncRNA may be a new potential biomarker for the clinical diagnosis of GC.